ID-based ring signature on prime order group from asymmetric pairing - Hongxia HOU; Mingrui ZHANG; Yanqi ZHAO; Xiaoli DONG (Tongxin xuebao)
For the problem that the security proof was difficult to be realized under the standard model in the existing ID-based ring signature schemes, an ID-based ring signature scheme proven secure in the standard model was proposed.Firstly, the formal definitions of security model and adversary model of ID-based ring signature were given.Then, a specific ID-based ring signature scheme was constructed on the prime order groups from asymmetric pairings.Finally, the security analysis and performance analysis were given.The results of security analysis show that the proven security of the proposed scheme is achieved under the standard model by using the dual system encryption technique.The results of performance analysis show that the operation efficiency of each algorithm in the proposed scheme is improved effectively, compared with existing ID-based ring signature schemes from dual system, it is shorter to take the time in generating and verifying signature.